2006
DOI: 10.1021/om060364l
|View full text |Cite
|
Sign up to set email alerts
|

Metallacumulenes as Potential Electron Reservoir Devices

Abstract: This paper reviews recent work in the area of organomanganese chemistry whose purpose is the design of single-molecule components for electronics. This field has recently received much attention in the pursuit of continued miniaturization of electronics. Electron reservoirs and molecular wires are basic motifs of single-electron devices. Both can accept and release electrons in a reversible fashion, but the former can also store electrons. Our recent work in the field deals with complexes of two distinct types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 171 publications
1
22
0
Order By: Relevance
“…[101] A particularly well-explored aspect of C-C coupling reactions in redox-generated organometallic radicals relates to the oxidation chemistry of the manganese vinylidene complexes depicted in Scheme 12. [102,103] The reaction of the vinylidene complex 13 with [FeCp 2 ]PF 6 at room temperature affords varying mixtures of the bis(carbyne) complexes 14 and 17. The reaction proceeds by the initial oxidation of the vinylidene to give the radical cation [13] ·+ , which may then undergo immediate C β -C β coupling to afford complex 14.…”
Section: Chemical Reactions Of σ-Alkynyl-based Radicals and Closely Rmentioning
confidence: 99%
“…[101] A particularly well-explored aspect of C-C coupling reactions in redox-generated organometallic radicals relates to the oxidation chemistry of the manganese vinylidene complexes depicted in Scheme 12. [102,103] The reaction of the vinylidene complex 13 with [FeCp 2 ]PF 6 at room temperature affords varying mixtures of the bis(carbyne) complexes 14 and 17. The reaction proceeds by the initial oxidation of the vinylidene to give the radical cation [13] ·+ , which may then undergo immediate C β -C β coupling to afford complex 14.…”
Section: Chemical Reactions Of σ-Alkynyl-based Radicals and Closely Rmentioning
confidence: 99%
“…Paramagnetic analogues of such species have electronic open-shell configurations and are therefore expected to have nonlinear optical properties in addition to having applications as electronic materials in single-electron devices [1][2][3]. Strongly r-donor ligandsubstituted complexes of this type are expected to have low energy work functions, which is expected to guarantee strong electronic delocalisation and coupling between the metal centres [34,35]. Only very recently a chromium bisacetylide complex has been reported [36].…”
Section: Introductionmentioning
confidence: 99%
“…Electron-rich manganese-centered vinylidene complexes have been exploited by many due to their low-energy work function. 16 Manganese vinylidene complexes of the type Mn(C 5 H 4 R′)(R′′ 2 PCH 2 CH 2 PR′′ 2 )dCdC(R 1 )(H) were designed and synthesized for application as molecular batteries. 16 Earlier reports by Terry et al 17 indicated that vinylidene complexes of the type Mn(C 5 H 5 )(CO) 2 dCdC(H) 2 were thermally unstable and thus had to be generated and studied at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…16 Manganese vinylidene complexes of the type Mn(C 5 H 4 R′)(R′′ 2 PCH 2 CH 2 PR′′ 2 )dCdC(R 1 )(H) were designed and synthesized for application as molecular batteries. 16 Earlier reports by Terry et al 17 indicated that vinylidene complexes of the type Mn(C 5 H 5 )(CO) 2 dCdC(H) 2 were thermally unstable and thus had to be generated and studied at low temperature. Later Venkatesan et al used bidentate phosphorus ligands Me 2 PCH 2 CH 2 PMe 2 (dmpe) and Et 2 PCH 2 CH 2 PEt 2 (depe) to obtain isolobal compounds that are thermally stable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation